2019
DOI: 10.1016/j.ajpath.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Is Important for Meibomian Gland Function as Revealed by a New Human ex Vivo Slice Culture Model

Abstract: Meibomian glands within the eyelid are important for the maintenance of the integrity and health of the ocular surface. Patients with the blistering skin disease pemphigus vulgaris (PV), which is caused by autoantibodies against desmosomal cadherins, often have dry eye disease. Therefore, we studied the regulation of cell cohesion in human meibomian gland epithelial cells (HMGECs). During serum-induced differentiation for 1 to 6 days, HMGECs drastically enhanced intercellular cohesion, whereas lipid production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…Recently, another in vitro slice culture model of the human eyelid was established for studying the function of E-cadherin on meibomian glands. 25 However, this method is not suitable for studying ductal system because it may damage the integrity of meibomian gland ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another in vitro slice culture model of the human eyelid was established for studying the function of E-cadherin on meibomian glands. 25 However, this method is not suitable for studying ductal system because it may damage the integrity of meibomian gland ducts.…”
Section: Discussionmentioning
confidence: 99%
“…The most highly expressed gene in the meibomian gland is the leukocyte-associated immunoglobulin-like receptor, an inhibitory receptor that inhibits immune cell activation and reduces the production of pro-inflammatory cytokines ( 80 ). Moreover, the immunoglobulin-like receptor gene expression is upregulated upon epithelial cell differentiation in the human meibomian gland ( 81 ). Recently, researchers have also found that human meibomian gland epithelial cell lysates inhibit the growth rate of gram-negative bacteria and pseudomonas aeruginosa ( 57 ).…”
Section: Immunomodulation Of Dry Eye Diseasementioning
confidence: 99%
“…Cadherins (subtypes of classical cadherins, E-, N-, and P-cadherin) are cell surface glycoproteins involved in calcium-dependent heterotypic and homotypic cell-cell adhesion ( 54 ). In one study, it was demonstrated that N-cadherin occurs in all layers of the cells in the skin epidermis, mucocutaneous junction, and conjunctiva ( 108 ). It is also present in the acini and ductal epithelium of the meibomian glands ( 54 , 108 ).…”
Section: Cadherins As Candidate Biomarkers For Meibomian Gland Dysfun...mentioning
confidence: 99%